Going from athlete-to-coach in Norwegian winter sports: understanding the transition journey - Chroni, S.; Pettersen, S.; Dieffenbach, K. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
Hiring retired athletes as coaches is a common practice that reinforces athletic experience as an important element of coaching, yet the coaching profession is complex, requiring specialized knowledge across multiple domains. This exploratory study scrutinizes the experiences of six Norwegian early career professionals who transited into coaching directly after the end of the elite athletic career in winter ski sports; focussing on how they constructed the narrative of the athlete-to-coach transition journey. Employing in depth interviews and thematic analysis we identified the themes of exiting the athletic career, entering coaching, the `no longer and not yet` in the transition, challenges and facilitators. These themes we transformed into (i) six stories, which provide multifaceted insights to the fast transiting of former athletes into coaching, and (ii) a three-phase empirical model, through theory-informed re-examination of the emergent themes based on career transition models. Recommendations for further understanding of this career pathway into coaching as well as the role of education and transition support programmes are explored.